Analysis Of Certification Policy Implementation - Ishak Kusnandar (STKIP Singkawang, 2018)
This study aims to find out and describe the implementation of Teacher Certification Policy in Madrasah Aliyah Negeri Sukamanah Tasikmalaya Regency. The approach used in this research is quantitative approach. The method used in this research is descriptive research method, that is research conducted to know the independent value, that is the variable of Implementation of Certification Policy at Madrasah Aliyah Negeri Sukamanah of Tasikmalaya Regency with analysis of implementation model of Edward III. The results showed that the Implementation of Certification Policy in Madrasah Aliyah Negeri Sukamanah Tasikmalaya Regency simultaneously is in the high category stage.